Functional identification of Annexin B1 and Annexin B2 from Cysticercus cellulosae and their mechanism in plasma membrane repair. - Peixia He; Dejia Zhang; Mengqi Wang; Rui Duan; Yuyuan Zhao; Sirui Wang; Xing Yang; Xiaolei Liu; Shumin Sun (PLoS Neglected Tropical Diseases)
Background Cysticercosis is a severe foodborne zoonotic parasitosis infected by the metacestode larvae of Taenia solium. However, its invasion mechanism is still not clear, which might provide the important evidence for treatment or vaccine. It was reported the annexin involved in the physiological and pathological functions of Cysticercus cellulosae. However, the regulatory mechanisms and roles of annexin B1 and annexin B2 in the invasion and immune escape of Cysticercus cellulosae have not been fully explored. Methods The annexin was acquired by cloning in prokaryotic expression vector, expressed in Escherichia coli, and purified by affinity chromatography. Its expression was determined by immunohistochemistry. The anticoagulant function and its underlying mechanism was verified by the determination of activated partial thromboplastin time, prothrombin time and phospholipid binding activity. The membrane repair function was verified by cell culture, transfection, and laser confocal technology. Results Immunohistochemistry results showed the B1 and B2 were mainly expressed on the body surface and the surface of digestive glands of Cysticercus cellulosae. The Blood coagulation results illustrated the B1 and B2 can prolong the time of both exogenous and endogenous coagulation pathways, with B2 having a more significant effect. They tend to bind to phosphatidylserine, possibly interfering with coagulation complex formation and inhibiting the coagulation pathway, and may assist in the worm's penetration through blood vessels and migration to parasitic sites. The plasma membrane repair test revealed the cells transfected with B1 and B2 genes have a significantly shorter plasma membrane repair time than the control group, suggesting that these proteins may be involved in repairing the worm's body surface to resist the immune system's attack when the host immune system attacks. Conclusions The Annexin B1 and Annexin B2 of Cysticercus cellulosae possess anticoagulant properties and can assist in membrane repair. Given these functions, it is speculated that they play a crucial role in immune evasion and invasion. However, further experiments are required to provide direct evidence to further validate these speculations.